PENGARUH CAMPURAN JENIS KAYU TERHADAP BEBERAPA SIFAT KAYU LAPIS*) - I M Sulastiningsih; Paribotro Sutjigno (Jurnal Penelitian Hasil Hutan, 1992)
Experimental   plywood (5 -  piy)  were made from  12 wood species  veneers  glued with  urea formaldehyde. Thichness of  veneer  was  1.5  mm  and  the  range  of  veneer  density   was  0.38  -   0.83 g/cm3.  Veneers  were divided  into  3 groups  based on  their  density,  i.e. low,   medium   and  high.  The  plywood properties   were  tested  according  to the  American Standard (ASTM)  and the  Japannese Standard  (JAS)  included  density.  tensile strength.  bending  strength, compression  strength,  and moisture  resistant  bonding  strength.The  results  revealed  that  plywood  density   was  higher  than  veneer  density   (same wood  species)  or average veneer density   (mixed  wood  species).   Tested  mechanical  properties of plywood  increased  if the plywood  density  increased and the relationship  could  be expressed  by  linier regression equations. The tensile strength, bending strength  and compression strength   of plywood  were  tested  both  on parallel and perpendicular to  face grain.  Correlation  coefficient  of  the relation-ship  between  plywood  density   and  those  plywood  mechanical  properties on parallel to face  grain (r = 0.66 -  0.84)  were higher  than  that  on perpendiculor  to face grain  (r = 0.51  -   0. 74). Similar results  were obtained  with F calculated  but all of  them  were  highly  significant.  Based on  those  results it could  be concluded   that some mechanical properties  of plywood could  be estimated   from  its  density, regardless   of  its wood  species.